Upregulated circTMEM59 Inhibits Cell Growth and Metastasis by miR-668-3p/ID4 Axis in Colorectal Cancer. (24th May 2022) - Feng, Yifei; Wang, Xiaoyuan; Huang, Changzhi; Zhang, Dongsheng; Liu, Tingwei; Zhang, Chuan; Zhang, Yue; Ji, Dongjian; Tang, Junwei; Sun, Yueming
Abstract : The incidence and mortality of colorectal cancer (CRC) are ranked in the top three worldwide in 2020. Abundant studies have reported that circular RNAs (circRNAs) act critical roles in the genesis and development of tumors, including CRC. Nevertheless, the roles and detailed regulation mechanisms of circRNAs that are related to the initiation and development of CRC have not been fully found and clarified. This research primarily revealed that circTMEM59 was greatly downregulated in CRC tissues and cell lines via qRT-PCR. In addition, the decreased expression of circTMEM59 was closely related to adverse clinicopathological characteristics and the shorter survival time of CRC patients. Then, a further study found that the overexpression of circTMEM59 suppressed cell growth and accelerated the cell death of CRC via a series of experiments in vitro and in vivo. Furthermore, circTMEM59 also repressed the metastatic behaviors of CRC cells. Further study revealed that circTMEM59 played the role of competing endogenous RNAs (ceRNAs) by binding to miR-668-3p to increase the expression of inhibitor of DNA binding 4 (ID4) in CRC. In summary, the results of this study clarified the antitumor effects of circTMEM59/miR-668-3p/ID4 axis in CRC progression and provided potential therapeutic targets and clinical prognostic markers for CRC.